2019
DOI: 10.3389/fcell.2019.00086
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Extracellular Matrix in Cancer Stemness

Abstract: As our understanding of cancer cell biology progresses, it has become clear that tumors are a heterogenous mixture of different cell populations, some of which contain so called “cancer stem cells” (CSCs). Hallmarks of CSCs include self-renewing capability, tumor-initiating capacity and chemoresistance. The extracellular matrix (ECM), a major structural component of the tumor microenvironment, is a highly dynamic structure and increasing evidence suggests that ECM proteins establish a physical and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
218
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(222 citation statements)
references
References 163 publications
(90 reference statements)
4
218
0
Order By: Relevance
“…GSEA results revealed that RP5-881L22.5 was likely to be involved in an extracellular matrix (ECM) interaction pathway. Glycoproteins make the ECM a cohesive network of molecules by linking cells together with structural components (Nallanthighal et al, 2019). Adhesive glycoproteins can bind to ECM components to activate downstream signaling pathways to regulate epithelial-mesenchymal transition, selfrenewal, migration, differentiation, and proliferation (Naba et al, 2016;Song et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…GSEA results revealed that RP5-881L22.5 was likely to be involved in an extracellular matrix (ECM) interaction pathway. Glycoproteins make the ECM a cohesive network of molecules by linking cells together with structural components (Nallanthighal et al, 2019). Adhesive glycoproteins can bind to ECM components to activate downstream signaling pathways to regulate epithelial-mesenchymal transition, selfrenewal, migration, differentiation, and proliferation (Naba et al, 2016;Song et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies have showed that ECM can serve as a niche for CSCs, providing structural and biochemical support to regulate proliferation, selfrenewal and differentiation of CSCs. 27 ECM stiffness as a physical properties of the ECM played a crucial role in regulating self-renewal and differentiation of CSCs through the formation of focal adhesions and subsequent activation of mechanotransduction pathways such as PI3K-AKT, Rho/ROCK, YAP/TAZ signaling pathway. [28][29][30] The above also confirmed our KEGG pathway enrichment analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is well established that the CSCs can reside in niches within the microenvironment [ 15 ] Moreover, the ECM niche provides structural support to the tissue and widely influences cell behavior [ 16 ]. The impact on the functional properties of CSCs is mediated by the interaction of the ECM with the cell surface receptors, specifically the integrin pathways [ 17 , 18 , 19 ].…”
Section: Extracellular Matrix As a Niche For Cancer Stem Cell Formmentioning
confidence: 99%
“…Integrins present on the surface of tumor and stromal cells are the primary receptors involved in cell–matrix adhesion and play a profound role in the ability of the CSCs to survive in specific locations. However, in some cases, these receptors can also function in the absence of ligand binding to promote stemness and survival in the presence of environmental and therapeutic stresses [ 19 ].…”
Section: Extracellular Matrix As a Niche For Cancer Stem Cell Formmentioning
confidence: 99%